1, 3-Dipolar cycloaddition of a cyclic nitrone derived from 2-deoxy-D-ribose to α, β-unsaturated lactones: An entry to carbapenem antibiotics. (4th October 2016) - Pieczykolan, Michał; Staszewska-Krajewska, Olga; Furman, Bartłomiej; Chmielewski, Marek
Abstract: 1, 3-Dipolar cycloadditions of 2-deoxy-D-ribose-derived L- threo five-membered cyclic nitrone to α, β -unsaturated γ - and δ -lactones were investigated. Cycloadducts obtained from δ -lactones, after N O bond cleavage, opening of the lactone ring, and protection of hydroxyl groups were subjected to β -lactam ring formation by using Mukaiyama's salt. Cycloadducts from γ -lactones subjected to the same reaction sequence undergo β -elimination of a water molecule to provide pyrrolidine-substituted unsaturated γ -lactones. Graphical abstract: Highlights: Stereoselective synthesis of izoxazolidine cycloadducts is described. Efficient and selective one-pot transformation in β -lactam structures is performed. Easy access to polyhydroxylated β -lactams is provided.